PENGARUH SIKAP WANITA USIA SUBUR TERHADAP KEPATUHAN DETEKSI DINI KANKER SERVIKS MELALUI PEMERIKSAAN IVA TEST DI PUSKESMAS HITU MALUKU TENGAH - Malawat, Ratna; Rahmawati, Wa Ode; Ratulohain, Christina (Poltekkes Kemenkes Maluku, 2025)
Cervical cancer in Indonesia is a big problem in health services because most patients come at an advanced stage. This is thought to be due to inadequate screening programs. IVA examination is a simple way to detect cervical cancer as early as possible with the aim of reducing the morbidity of the disease by early treatment of cases found to identify abnormalities in the cervix. However, the examination can be an obstacle due to the mother's lack of compliance with this examination. The public interest in this examination is that most women are afraid to undergo the examination, apart from being embarrassed about their intimate organs, women are also afraid of the results they will obtain during the examination. This study aims to determine the influence of WUS attitudes towards compliance in participating in early detection of cervical cancer through the IVA test at the Hitu Community Health Center, Central Maluku Regency. The type of research used was analytical observational with a cross sectional research design, while the data analysis used was univariate and bivariate analysis with the Chi Square test. The research results found were that the majority expressed a positive attitude of 72%, the majority were willing to undergo an IVA examination, namely 30 people (60%). Based on statistical tests using the Chi-Square test, the p value was 0.000, where the p value < α (0.000 < 0, 05). The conclusion in this study is that there is an influence between WUS attitudes on compliance in participating in early detection of cervical cancer through VIA examinations at the Hitu Community Health Center, Central Maluku Regency. It is recommended that WUS want to carry out an IVA test and that health workers continue to provide health education about preventing cervical cancer through a healthy lifestyle and early detection through an IVA test. Keyword: Woman. Attitude. Compliance. IVA Test